A study on awareness of architects and local authority towards the CCC / Mohd Hafiz Faizal Ibrahim - Ibrahim, Mohd Hafiz Faizal (Faculty of Architecture, Planning and Surveying, 2008)
The Completed of Certificate and Compliance (CCC) replaces the Certificate of Fitness for Occupation (CFO) previously issued by the local authority (PBT). The project’s Principal Submitting Person (PSP) who is a Professional Architect, Professional Engineer or a Registered Building Draughtsman allowed by the Architects Act to issue a CCC for buildings not exceeding two storey’s and an area less than 300 square meters issues the CCC. However, since launched on April 2007, the implementation of the CCC is still not enough. Base on the pilot study done before, some of people in the local authority, architect and public still not aware of this implementation. Although local authority has started the implementation of this system since a year ago, this new system still has very low awareness among the contractors. It is the government’s view that CCC will cut down on not important procedure and ensure that house buyers and building owners get to move in as quickly as possible without compromising their safety. This is consistent with the government’s desire to encourage selfregulation, which is introduced in the National Economy Growth Planning strategy to continuously enhance the delivery system.